PENGARUH PRODUKSI DAN PRODUKTIVITAS PETANI TERHADAP IMPOR JAGUNG DI INDONESIA TAHUN 1993-2018 - Zahara Zahara; Devi Andriyani; Reza Juanda (LPPM Universitas Malikussaleh – Indonesia, 2021)
This research aims to analyze the effect of corn production and productivity of maize farmers on imports in Indonesia in 1993-2018. The data used in this research are secondary data for the 1993-2018 period. This research model uses multiple linear regression. The results of the research that corn production partially has a negative effect on corn imports in Indonesia. Rice farmer productivity has a positive effect on corn imports in Indonesia. Simultaneously, maize production and productivity of maize farmers have an effect on maize imports in Indonesia